2018
DOI: 10.1007/s12571-018-0850-z
|View full text |Cite
|
Sign up to set email alerts
|

Addressing food poverty in systems: governance of food assistance in three European countries

Abstract: Italy), where she teaches a masters' course on policies for the food system policies. She completed a Ph.D. in 'Economics and Territory', University of Tuscia (Viterbo, Italy) with a thesis on multicriteria assessment of impacts on the EU food quality polity and Geographical Indications. She continued to worked for six years as a post doctoral researcher (University of Pisa, Italy) on European FP7 and H2020 multi actor research projects (FOODLINKS; GLAMUR; TRANSMANGO, SALSA, ROBUST). Her research interests foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 66 publications
0
33
0
Order By: Relevance
“…From the side of poverty alleviation, (unavoidable and avoidable) surplus food is valuable. It is among the resources streams that support food banks capacity (with differences according to the food assistance governance models (Galli et al 2018)). Third sector reliance (or dependency) on surplus food should be considered carefully (e.g.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 3 more Smart Citations
“…From the side of poverty alleviation, (unavoidable and avoidable) surplus food is valuable. It is among the resources streams that support food banks capacity (with differences according to the food assistance governance models (Galli et al 2018)). Third sector reliance (or dependency) on surplus food should be considered carefully (e.g.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…From 2015 to 2017 in-depth interviews with food banks leaders and workshops have been developed with reference to the Italian context. More details on the empirical studies can be found in Galli et al (2018Galli et al ( , 2016 and Arcuri et al (2016).…”
Section: System Dynamics Conceptual Mapping: Methodology and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Galli et al, develop a system dynamics conceptualization of food waste generation, food recovery and redistribution for social purposes. Food assistance is qualified as a hybrid system, spanning food, public welfare and the voluntary sectors (Galli et al 2018). The analysis of feedback interactions highlights the (actual and potential) vulnerabilities of food assistance systems that occur when addressing food poverty by reducing food surplus.…”
mentioning
confidence: 99%